Evaluation of bioaccumulation of nanoplastics, carbon nanotubes, fullerenes, and graphene family materials. (March 2023) - Petersen, Elijah; Barrios, Ana C.; Bjorkland, Rhema; Goodwin, David G.; Li, Jennifer; Waissi, Greta; Henry, Theodore
Graphical abstract: Abstract: Bioaccumulation is a key factor in understanding the potential ecotoxicity of substances. While there are well-developed models and methods to evaluate bioaccumulation of dissolved organic and inorganic substances, it is substantially more challenging to assess bioaccumulation of particulate contaminants such as engineered carbon nanomaterials (CNMs; carbon nanotubes (CNTs), graphene family nanomaterials (GFNs), and fullerenes) and nanoplastics. In this study, the methods used to evaluate bioaccumulation of different CNMs and nanoplastics are critically reviewed. In plant studies, uptake of CNMs and nanoplastics into the roots and stems was observed. For multicellular organisms other than plants, absorbance across epithelial surfaces was typically limited. Biomagnification was not observed for CNTs and GFNs but were observed for nanoplastics in some studies. However, the reported absorption in many nanoplastic studies may be a consequence of an experimental artifact, namely release of the fluorescent probe from the plastic particles and subsequent uptake. We identify that additional work is needed to develop analytical methods to provide robust, orthogonal methods that can measure unlabeled (e.g., without isotopic or fluorescent labels) CNMs and nanoplastics.